2018
DOI: 10.1186/s12864-018-4720-z
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly and positive selection analysis of an individual deep-sea fish

Abstract: BackgroundHigh hydrostatic pressure and low temperatures make the deep sea a harsh environment for life forms. Actin organization and microtubules assembly, which are essential for intracellular transport and cell motility, can be disrupted by high hydrostatic pressure. High hydrostatic pressure can also damage DNA. Nucleic acids exposed to low temperatures can form secondary structures that hinder genetic information processing. To study how deep-sea creatures adapt to such a hostile environment, one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 63 publications
6
49
0
Order By: Relevance
“…Furthermore, an additional ribosomal protein was positively selected in Ophiodermatidae and two transcription factors were positively selected in Amphiuridae. Previous studies have shown that several genes involved in genetic information processing such as protein folding, transcription or translation (including ribosomal proteins) were positively selected in the hadal (>6000m depth) amphipod Hirondella gigas (Lan et al 2017), in the bathyal (200-3000m depth) fish Aldrovandia affinis (Lan et al 2018) and in the bathyal barnacle Glyptelasma gigas (Gan et al 2020). Taken together, these and previous results indicate that adaptations in protein biogenesis are essential to deep-sea life.…”
Section: Protein Biogenesis Is Essential For Deep-sea Adaptationsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, an additional ribosomal protein was positively selected in Ophiodermatidae and two transcription factors were positively selected in Amphiuridae. Previous studies have shown that several genes involved in genetic information processing such as protein folding, transcription or translation (including ribosomal proteins) were positively selected in the hadal (>6000m depth) amphipod Hirondella gigas (Lan et al 2017), in the bathyal (200-3000m depth) fish Aldrovandia affinis (Lan et al 2018) and in the bathyal barnacle Glyptelasma gigas (Gan et al 2020). Taken together, these and previous results indicate that adaptations in protein biogenesis are essential to deep-sea life.…”
Section: Protein Biogenesis Is Essential For Deep-sea Adaptationsupporting
confidence: 76%
“…Patterns of positive selection have been investigated to uncover genes underlying adaptation to specific environments, including the deep-sea, in non-model species Lan et al 2018;Oliver et al 2010;Sun et al 2017;Zhang et al 2017;Weber et al 2017). Although valuable, these studies typically focus on a single or few shallow-deep transitions in a limited number of species, and thus lack the comparative power to separate confounding effects.…”
Section: Introductionmentioning
confidence: 99%
“…But for the second calculation, the reads of each tissue were separately mapped to the clean transcripts with an open reading frame to quantify the gene-level abundance of each gene in each tissue. In detail, to remove the assembly error, the transcripts with a TPM value below 0.1 were eliminated as in our previous studies (Lan et al, 2017(Lan et al, , 2018. The isoforms with the highest TPM value were retained to predict genes.…”
Section: Functional Annotation and Identification Of Highly Expressedmentioning
confidence: 99%
“…Therefore, the default pairwise similarity threshold of PosiGene (Sahm et al, 2017a) was applied to remove alignment errors, such as orthologs that were pseudo or poorly aligned, and nominal P-values were directly used to identify positively selected genes (Fletcher and Yang, 2010;Sahm et al, 2017b). If the genes had a P-value below 0.05 and amino acid sites with a bayes empirical bayes (BEB) probability above 0.9, they were regarded as the positively selected genes (Lan et al, 2017(Lan et al, , 2018Sun et al, 2017). For the positive selection analysis of symbionts, the settings of PosiGene was -target_species = symbiont Candidatus Vesicomyosocius okutanii, -anchor species = symbiont Candidatus Vesicomyosocius okutanii, -min_seq_num = 3, -min_omega = 0, -min_site_signifance = 0.9.…”
Section: Positive Selection Analysismentioning
confidence: 99%
“…Conditions on the deep-sea floor are poorly known but generally are considered too harsh for the survival of most organisms, e.g., high hydrostatic pressure, darkness, hypoxia, low temperature, and limited food availability [1][2][3][4][5]. However, a macrofauna consisting of a growing range of newly discovered animals adapted to deep-sea habitats has been reported, including crustaceans [6][7][8], polychaetes [9,10], fishes [11,12], and mollusks [13,14]. Various mechanisms have adapted them for survival in deep-sea environments: e.g., squat lobsters and mussels have developed chemoautotrophic systems of symbiotic bacteria for inhabiting hydrothermal vents and cold seeps in the seafloor [15][16][17]; and snailfish have evolved special morphological and physiological characters to survive and thrive in the hadal zone [12].…”
Section: Introductionmentioning
confidence: 99%